PENGARUH STRATEGI PROMOSI, PERSEPSI DAN FLUKTUASI HARGA EMAS TERHADAP KEPUTUSAN NASABAH MENGGUNAKAN PRODUK CICIL EMAS SOLEH PADA BANK MUAMALAT: (Studi Kantor Cabang Bank Muamalat Karanganyar) - Annisa Griseldawati; Agung Abdullah (JURNAL ILMIAH EDUNOMIKA, 2026)
The most number of expansion Islamic banking in Indonesia encourages financial institutions to innovate in offering investment products based on real assets such as gold instalment schemes. In this context, Bank Muamalat as the first Islamic Bank in country, introduced the Solusi Emas Hijrah (SOLEH) product as an alternative for customers who want to own gold gradually in accordance with sharia principles. This research aims to reveal what strategies will be used by banks to get consumers, because almost all Islamic banks also offer similar products. The result showed the influence of Promotion Strategy, Perception, and Gold Price Fluctuations on Customer Decisions to Use the Gold Installment Product, Solusi Emas Hijrah (SOLEH) at Bank Muamalat is positive and significant.